Analysis Of The Use Of Technical Indicators And Trendlines In Maximizing Stock Investment Profits In The Capital Market Indonesia (The Manager Review, 2025)
This study aims to analyze the effectiveness of stock investment in the Indonesian capital market using a descriptive quantitative approach. This study uses historical stock price data and various technical indicators, such as Exponential Moving Average (EMA), Stochastic Oscillators, and Trendlines, to determine the optimal investment strategy. By using a descriptive quantitative method, this study aims to investigate the status, condition, or predict future events factually, systematically, and accurately. This study uses data from 31 issuers that meet the Purposive sampling criteria, taken from the LQ45 index and have been listed on the Indonesia Stock Exchange since 2017. The data analyzed covers a 5-year period from 2018 to 2022, with a total of 1219 days. Data analysis was carried out using Eviews 9 software, focusing on the percentage of profit/loss from the buy and sell signals that appeared. The results of direct testing show that EMA and SO have a significant positive effect on MP, while TL does not show a significant effect. The Sobel test to test the mediation effect shows that EMA mediated by TL has a significant positive effect on MP, while SO mediated by TL shows a negative effect. The discussion of these results emphasizes that EMA and SO can help investors in identifying market trends and momentum, thus enabling them to make better and more optimal investment decisions.